Deletion of Endonuclease V suppresses chemically induced hepatocellular carcinoma. Issue 8 (21st February 2020) - Kong, Xiang Yi; Vik, Erik Sebastian; Nawaz, Meh Sameen; Berges, Natalia; Dahl, Tuva Børresdatter; Vågbø, Cathrine; Suganthan, Rajikala; Segers, Filip; Holm, Sverre; Quiles-Jiménez, Ana; Gregersen, Ida; Fladeby, Cathrine; et al.
Abstract: Endonuclease V (EndoV) is a conserved inosine-specific ribonuclease with unknown biological function. Here, we present the first mouse model lacking EndoV, which is viable without visible abnormalities. We show that endogenous murine EndoV cleaves inosine-containing RNA in vitro, nevertheless a series of experiments fails to link an in vivo function to processing of such transcripts. As inosine levels and adenosine-to-inosine editing often are dysregulated in hepatocellular carcinoma (HCC), we chemically induced HCC in mice. All mice developed liver cancer, however, EndoV −/− tumors were significantly fewer and smaller than wild type tumors. Opposed to human HCC, adenosine deaminase mRNA expression and site-specific editing were unaltered in our model. Loss of EndoV did not affect editing levels in liver tumors, however mRNA expression of a selection of cancer related genes were reduced. Inosines are also found in certain tRNAs and tRNAs are cleaved during stress to produce signaling entities. tRNA fragmentation was dysregulated in EndoV −/− livers and apparently, inosine-independent. We speculate that the inosine-ribonuclease activity of EndoV is disabled in vivo, but RNA binding allowed to promote stabilization of transcripts or recruitment of proteins to fine-tune gene expression. The EndoV −/− tumor suppressive phenotype calls for related studies in human HCC.